2015
DOI: 10.1111/are.12947
|View full text |Cite
|
Sign up to set email alerts
|

Is pearl colour produced fromPinctada margaritiferapredictable through shell phenotypes and rearing environments selections?

Abstract: The black-lipped pearl oyster, Pinctada margaritifera, is the most important farmed mollusc species in French Polynesia. Donor oyster selection among wild P. margaritifera individuals, chosen according to their inner shell colour, makes it possible to obtain the broadest range of cultured pearl colours of any species. This study demonstrates the relative influence of using black [B] or red [R] outer shell phenotypes, combined with green [G] or yellow [Y] inner shell phenotypes, on pearl darkness level, colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In addition, a study of the digital colour of P. fucata martensii has shown that the nacre colour of the donor oysters contributes to the resulting pearl colour (Gu, Huang, Wang, Gan, Zhan, Shi & Wang ). Recently, the pearl colour in P. margaritifera was demonstrated definitively to be related to the inner shell phenotype colouration of the donor (Ky, Le Pabic, Sham‐Koua, Okura, Molinari, Nakasai & Devaux ). For the same wild spat collection location, frequency of colourful inner shells was higher in young individuals than in older ones.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of the digital colour of P. fucata martensii has shown that the nacre colour of the donor oysters contributes to the resulting pearl colour (Gu, Huang, Wang, Gan, Zhan, Shi & Wang ). Recently, the pearl colour in P. margaritifera was demonstrated definitively to be related to the inner shell phenotype colouration of the donor (Ky, Le Pabic, Sham‐Koua, Okura, Molinari, Nakasai & Devaux ). For the same wild spat collection location, frequency of colourful inner shells was higher in young individuals than in older ones.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ky et al . () also revealed correlations between the outer and inner shell colours of donors and the colour proportions observed in the harvested pearls. Whereas shell morphology is a species‐specific characteristic, shell colour varies very widely among P. margaritifera individuals used as donors, allowing the production of an equally broad spectrum of pearl colours.…”
Section: Pinctada Margaritifera Flesh and Shell Colour Phenotypes Of mentioning
confidence: 76%
“…Although only a few studies have been made on transmissions between donor phenotypes and pearl colours in P. margaritifera, these relations have been demonstrated through experimental grafting designs using both wild (Tayale et al, 2012) and hatchery-produced (Ky et al, 2013;2016a) donor oysters. More recently, Ky et al (2015a) also observed correlations between the outer (prismatic layers) and inner (nacreous layers)…”
Section: Introductionmentioning
confidence: 77%